The determinants of Brazilian corporate credit ratings: how did the market react to sovereign downgrades? - Rocca, Nicolò (2017)
The first purpose of this research is to study which are the main determinants of the changes of Brazilian corporate credit ratings provided by Standard & Poor’s. Panel regressions are applied in order to analyze the relations between ratings and seven determinants. Results show five statistically significant determinants. The second part of the study examines how Brazilian listed companies reacted to the recent sovereign downgrades issued by Standard & Poor, Moody’s and Fitch. Event study methodology is used. All the events deliver empirical evidences of negative abnormal returns, showing a strong negative correlation between the credit rating negative actions and the Brazilian stock market. When aggregating the events, downgrades to junk territory and Moody’s rating’s changes are the ones upsetting stocks returns the most.